2002
DOI: 10.5194/angeo-20-967-2002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for acceleration of outer zone electrons to relativistic energies by whistler mode chorus

Abstract: Abstract. We use plasma wave and electron data from the Combined Release and Radiation Effects Satellite (CRRES) to investigate the viability of a local stochastic electron acceleration mechanism to relativistic energies driven by gyroresonant interactions with whistler mode chorus. In particular, we examine the temporal evolution of the spectral response of the electrons and the waves during the 9 October 1990 geomagnetic storm. The observed hardening of the electron energy spectra over about 3 days in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 36 publications
2
119
0
Order By: Relevance
“…Whistler mode waves are known to be substorm-dependent (e.g. Tsuratani and Smith, 1977;Meredith et al, 2001) and have recently been observed in association with the generation of outer zone relativistic electrons (Meredith et al, 2002a(Meredith et al, , 2002b, lending credence to this proposed mechanism. However, ULF waves have also been invoked as a means of accelerating the seed electrons to MeV energies.…”
Section: Discussionmentioning
confidence: 76%
“…Whistler mode waves are known to be substorm-dependent (e.g. Tsuratani and Smith, 1977;Meredith et al, 2001) and have recently been observed in association with the generation of outer zone relativistic electrons (Meredith et al, 2002a(Meredith et al, , 2002b, lending credence to this proposed mechanism. However, ULF waves have also been invoked as a means of accelerating the seed electrons to MeV energies.…”
Section: Discussionmentioning
confidence: 76%
“…High-energy electron enhancements last longer and are confined to a narrower L range within $3-6 with the same exception during major storms after the two equinoctial points, when MeV electrons can reach lower L-shells. Figure 5d highlights the high-energy electron fluxes at or higher than the 95th percentile given by LEEM, which appear highly correlated to strong and prolonged enhancements in low-energy electron levels as suggested by Meredith et al [2002]. The inner belt region (L < 2) is generally stable for both low-and highenergy electrons with no significant enhancement during 2001.…”
Section: Qualitative Discussion Of Leem Resultsmentioning
confidence: 92%
“…Meredith et al (2001) analyzed electric field measurements of the CRRES spacecraft and observed equatorial chorus with average amplitudes E w of the order of 1 mV/m during geomagnetic substorms. The plasma frequency f p has been estimated for these conditions from wave measurements, yielding the ratio to the electron cyclotron frequency f p /f c between 1 and 5 (Meredith et al, 2002). This, using the cold plasma theory in the frequency range of lower-band chorus (f =0.1-0.5 f c ), gives the refractive index of parallel propagating whistler-mode waves,…”
Section: Expected Amplitudes Of Nonlinear Chorus Wave Packetsmentioning
confidence: 99%